Does awareness on health hazards of tobacco use promote quit attempt? An observational study from urban Pondicherry - Naik, Bijaya N.; Kar, Sitanshu S.; Majella, Marie G.; S., Parthibane (International Journal Of Community Medicine And Public Health, 2017)
Tobacco use is the most prevalent behavioural risk factors for non-communicable diseases. In rural Pondicherry, the willingness to quit is low despite higher proportion of tobacco users being aware of health hazards of tobacco use. Hence, this observational study was conducted with the aim to assess the awareness on health hazards of tobacco use and quit attempt among the tobacco users attending an urban health centre in Pondicherry. A total of 90 individuals above 15 years of age attending the centre for treatment were included in the study and interviewed after obtaining verbal informed consent. Socio-demographic details, awareness on health hazards of tobacco use, quit attempts and reasons for failed quit attempt were noted down using a semi-structured questionnaire. Majority (64.4%, 58/90) of the current smokers were aware of health hazards related to tobacco use. Only one third of the tobacco users had tobacco quit attempt. Tobacco quit attempt recorded to be significantly (p value < 0.05) higher among people who were aware of health hazards (50%, 29/58) than the people who were not aware of health hazards (12.5%, 4/32). Creating awareness on health hazards and providing personalized counselling services to address reasons for failed quit attempt will improve the successful quitting of tobacco use.